Enhancing Patient Outcomes Through Team-Based Care: A Review of Integrated Practices Among Doctors, Family Physicians, Nurses, and Health Assistants - Alsaedi, Mohammed Faleh; Aljohani, Nawaf Mohammed; Alzaide, Maraim Abdullah; Alsuhaymi, Awatef; Almushdak, Abdulelah Olithah; Aljohani, Hissah Homowd E.; Aljohani, Nouf Sayah; Aljohani, Laila Faleh; Alblowey, Hanna Falah; Alsaedi, Sara Faleh (Journal of Posthumanism, 2024)
Introduction: A patient-centered approach, team-based care brings together various medical professionals to handle complicated patient requirements. It enhances clinical results and patient satisfaction while guaranteeing coordinated, ongoing, and comprehensive care.Aim of work: Examining how integrated healthcare teams improve patient outcomes and care quality is the goal of this study. Additionally, it looks for operational advantages and challenges in putting collaborative care models into practiceMethods: A literature review was conducted using databases like PubMed and Scopus, targeting studies from 2023–2024. Thematic analysis identified patterns in outcomes, benefits, and challenges of team-based care models.Results: Team-based care improves clinical outcomes, patient satisfaction, and continuity of care while reducing readmission rates. Challenges include communication barriers, unclear roles, and institutional resistance.Conclusion: Team-based care models enhance patient care, reduce errors, and improve healthcare delivery efficiency. Future adoption requires better communication, policy support, and interprofessional training.